The Look of (Un)confidence: Visual Markers for Inferring Speaker Confidence in Speech - Mori, Yondu; Pell, Marc D. (Frontiers in Communication, 2019)
Evidence suggests that observers can accurately perceive a speaker’s static confidence level, related to their personality and social status, by only assessing their visual cues. However, less is known about the visual cues that speakers produce to signal their transient confidence level in the content of their speech. Moreover, it is unclear what visual cues observers use to accurately perceive a speaker’s confidence level. Observers are hypothesized to use visual cues in their social evaluations based on the cue’s level of perceptual salience and/or their beliefs about the cues that speakers with a given mental state produce. We elicited high and low levels of confidence in the speech content by having a group of speakers answer general knowledge questions ranging in difficulty while their face and upper body were video recorded. A group of observers watched muted videos of these recordings to rate the speaker’s confidence and report the face/body area(s) they used to assess the speaker’s confidence. Observers accurately perceived a speaker’s confidence level relative to the speakers’ subjective confidence, and broadly differentiated speakers as having low compared to high confidence by using speakers’ eyes, facial expressions, and head movements. Our results argue that observers use a speaker’s facial region to implicitly decode a speaker’s transient confidence level in a situation of low-stakes social evaluation, although the use of these cues differs across speakers. The effect of situational factors on speakers’ visual cue production and observers’ utilisation of these visual cues are discussed, with implications for improving how observers in real world contexts assess a speaker’s confidence in their speech content.